A prospective evaluation of the impact of individual RF applications for slow pathway ablation for AVNRT: Markers of acute success. (3rd May 2021) - Sugumar, Hariharan; Chieng, David; Prabhu, Sandeep; Voskoboinik, Aleksandr; Anderson, Robert D; Al‐Kaisey, Ahmed; Lee, Geoffrey; McLellan, Alex J; Morton, Joseph B; Taylor, Andrew J; Ling, Liang‐Han; Kalman, Jonathan M; et al.
Abstract: Background: Catheter ablation is highly effective for atrioventricular nodal re‐entrant tachycardia (AVNRT). Generally junctional rhythm (JR) is an accepted requirement for successful ablation however there is a lack of detailed prospective studies to determine the characteristics of JR and the impact on slow pathway conduction. Methods: Multicentre prospective observational study evaluating the impact of individual radiofrequency (RF) applications in typical AVNRT (slow/fast). Characteristics of JR during ablation were documented and detailed testing was performed after every RF application to determine outcome. Procedural success was defined as ≤1 AV nodal echo. Results: Sixty‐seven patients were included (mean age 53 ± 18years, 57% female and a history of SVT 2.9 ± 4.7 years). RF (50w, 60°) ablation for AVNRT was applied in 301 locations with JR in 178 (59%). Successful slow pathway modification was achieved in 66 (99%) patients with slow pathway block in 30 (46%). Success was associated with JR in all patients. Success was achieved in six patients with RF < 10 s. There was no significant difference in the CL of JR during RF between effective (587 ± 150 ms) versus ineffective (611 ± 193 ms, p  = .4) applications. Inadvertent junctional beat‐atrial (JA) block with immediate termination of RF was observed in 19 (28%) patients with AVNRT no longer inducible in 14 (74%). Freedom from SVT was achieved in 66 (99%) patients at a mean follow up of 15 ± 6 months. Conclusion: In this prospective study, JR was required during RF for acute success in AVNRT. Cycle length of JR during RF was not predictive of success. Although unintended JA block during faster JR was associated with slow pathway block, this is a precursor to fast pathway block and should not be intentionally targeted.